2020
DOI: 10.1186/s12891-020-03270-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shockwave therapy on musculoskeletal conditions based on changes in imaging: a systematic review and meta-analysis with meta-regression

Abstract: Background: Shockwave therapy (SWT) is a commonly used intervention for a number of musculoskeletal conditions with varying clinical outcomes. However, the capacity of SWT to influence pathophysiological processes and the morphology of affected tissues remains unclear. The objective of the current review is to evaluate changes in imaging outcomes of musculoskeletal conditions following SWT. Methods: A comprehensive search of Medline, Embase, Cochrane Controlled Trials Register, CINAHL and SportDiscus was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
0
20
0
2
Order By: Relevance
“…Two reviews investigated the effect of shockwave therapy in soft tissue [55] or musculoskeletal [57] conditions and discussed plantar fasciitis separately in their reviews. Speed conducted a systematic review including 12 RCTs without meta-analysis and concluded that high-dosed focused ESWT and radial shockwave have benefits in pain reduction at 12 weeks [55].…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two reviews investigated the effect of shockwave therapy in soft tissue [55] or musculoskeletal [57] conditions and discussed plantar fasciitis separately in their reviews. Speed conducted a systematic review including 12 RCTs without meta-analysis and concluded that high-dosed focused ESWT and radial shockwave have benefits in pain reduction at 12 weeks [55].…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
“…Speed conducted a systematic review including 12 RCTs without meta-analysis and concluded that high-dosed focused ESWT and radial shockwave have benefits in pain reduction at 12 weeks [55]. Al-Abbad et al performed a meta-analysis of seven studies and showed an overall reduction in plantar fascia thickness after ESWT at 4 weeks, 6 weeks, 3 months, and 6 months, and a greater reduction was found when radiologic guidance was used [57].…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
“…The articles published in this Article Collection clearly show the efforts of researchers to find innovative applications of musculoskeletal imaging in clinical practice and to face the crucial challenges that remain in the interpretation and quality control of images. Indeed, highly performing diagnostic technologies are currently available to early diagnose and accurately monitor several musculoskeletal disorders [ 1 3 ], but also to guide personalized interventional therapeutic procedures tailored to the individual patients in the emerging process of precision medicine [ 4 7 ]. Among these new modalities, some are particularly promising and thereby subject to several lines of research in RMDs, including SPECT-CT and dual-energy CT [ 8 , 9 ], novel MRI sequences [ 10 12 ], high and ultra-high frequency ultrasound with effective tools like shear wave elastography [ 13 16 ].…”
Section: Main Textmentioning
confidence: 99%
“…As mentioned above, US-PICT and ESWT are the most commonly used procedures to treat RCCT. Previous studies have used CR and/or US to assess imaging response to treatment [ 45 ]. Most studies demonstrated a progressive and complete resorption of calcific deposits, while a minor part of authors reported the fragmentation or significant reduction of calcium deposit size already after 1 week [ 46 ], 3 months [ 47 ], and 12 months [ 48 , 49 ].…”
Section: Usual Imaging Findings Of Rcctmentioning
confidence: 99%
“…Notably, total calcium resorption has been reported to be higher after US-PICT than ESWT [ 48 , 49 ]. Furthermore, pre-treatment calcification size seems to be an independent predictor for changes in imaging outcomes after ESWT [ 45 ].…”
Section: Usual Imaging Findings Of Rcctmentioning
confidence: 99%